PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN ONLINE BUSANA MUSLIM DI INDUSTRI NANAD HIJAB CIBINONG BOGOR - Hari Subagyo, Wawan; Safitri, Yulia (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2019)
Fashion muslim development in the country rapid progress. Because many women in awareness muslim clothed covered in accordance with what god, make and it has now become a muslim needs. This impact for the entrepreneur the clothing industry for a racing in creating innovation and producing muslim clothes. Research aims to understand the influence of, products , price , promotion and a partial and in simultaneous with the resolution of the purchase of products in the Nanad Hijab Industry. This type of research is causal research with quantitative methods. The population of this study includes consumers who buy Nanad Hijab products online through the Shopee application with a sample of 80 respondents. Methods of collecting data through questionnaires. The analysis used is the validity, reliability test, analysis linear regression multiple, the assumption classical , and the hypothesis. The results showed that Product Variables had a significant effect on the Muslim Muslim online purchasing decisions in the Nanad Hijab Cibinong Industry, Price Variables had a significant effect on the Muslim Muslim online purchase decision in the Nanad Hijab Cibinong Industry, Promotion Variables had a significant effect on Muslim fashion online purchasing decisions at the Nanad Hijab Industry Cibinong. The Marketing Mix jointly influences the decision to purchase Muslim fashion online at the Nanad Hijab Cibinong Industry.